A new species of the genus Telomerina Roháček, 1983 (Diptera, Sphaeroceridae) from North-east China, with a key to the known species of Telomerina. (2nd October 2017) - Su, Lixin; Xu, Jie; Cong, Guoyi
Abstract: One new species, Telomerina wulongensis Su, is described and illustrated in the present study. Its phylogenetic relationships are discussed and a key to the known worldwide species of Telomerina is provided. Type specimens of T. wulongensis have been deposited in Liaoning Key Laboratory of Urban Integrated Pest Management and Ecological Security, Shenyang University, Shenyang, Liaoning, China. http://www.zoobank.org/urn:lsid:zoobank.org:pub:4442FAB4-AF4B-4ABE-8D19-E47D1D068E0D